1996
DOI: 10.1128/cdli.3.4.477-479.1996
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neutralizing antibody to respiratory syncytial virus in sera from mothers and newborns residing in the Gambia and in The United States

Abstract: The prevalence of maternal respiratory syncytial virus (RSV)-neutralizing antibodies has been documented in developed countries, but there is little information from developing countries. We assessed the prevalence of RSV-neutralizing antibody in sera from Gambian women and their newborns and compared them with their American counterparts during a similar period. The geometric mean titers of maternal antibodies to RSV subgroup A in the two populations were similar, while titers of antibodies to RSV subgroup B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…These results are slightly lower compared to those found in a recent study conducted in Bangladesh [19] . However, other studies reported neutralising antibody titres lower than our estimates [20,21] . We also found that, the cord antibody level is related to birthweight and gestational period; which are some of the factors reported to influence transplacental antibody transfer [22] .…”
Section: Discussioncontrasting
confidence: 93%
“…These results are slightly lower compared to those found in a recent study conducted in Bangladesh [19] . However, other studies reported neutralising antibody titres lower than our estimates [20,21] . We also found that, the cord antibody level is related to birthweight and gestational period; which are some of the factors reported to influence transplacental antibody transfer [22] .…”
Section: Discussioncontrasting
confidence: 93%
“…Therefore, pertussis vaccines in pregnancy are administered in the third trimester to maximize transplacental antibody transfer to the infant [ 19 ]. RSV transplacental antibody transfer is efficient in mother-infant pairs in South Asia, the United States, and the Gambia [ 20 ]. Higher cord blood RSV antibody titers in Bangladesh are associated with decreased risk of serologic infection in infants [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Passively acquired IgG RSV antibodies decline progressively during the first months of life, with a halflife of 26 days [Brandenburg et al, 1997]. Data from developing countries are scarce but would indicate that transmission of antibodies across the placenta and the kinetics of antibody decline are similar to those in developed regions [Suara et al, 1996].…”
Section: Introductionmentioning
confidence: 99%